Police Legitimacy in the Context of Street Stops: The Effects of Race, Class, and Procedural Justice: - Henry, Tri Keah S. (Criminal justice policy review, 2019)
Citizens’ perceptions of the police have been recognized as a long-standing issue of significant importance. Positive perceptions of the police, especially as they relate to legitimacy, are not only critical for fostering healthy police/community relationships but also for enhancing community safety. A large body of research has examined the predicates of legitimacy by studying residents’ general police perceptions as well as their perceptions in specific contexts, primarily traffic stops. Much less is known, however, about the sources of police legitimacy in the context of street stop encounters. Consequently, the current study uses data from the 2011 Police Public Contact Survey to examine the role of procedural justice, along with key sociodemographic characteristics—race and class—in shaping perceptions of legitimacy during non-traffic-related police-citizen street encounters. Findings indicate that officer behavior and levels of respect afforded to citizens during these encounters significantly influence perceptions of legitimacy. Implications and policy recommendations are discussed in detail.